If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -12 + 2p = 6 + 3p + -11 Reorder the terms: -12 + 5p + 2p = 6 + 3p + -11 Combine like terms: 5p + 2p = 7p -12 + 7p = 6 + 3p + -11 Reorder the terms: -12 + 7p = 6 + -11 + 3p Combine like terms: 6 + -11 = -5 -12 + 7p = -5 + 3p Solving -12 + 7p = -5 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. -12 + 7p + -3p = -5 + 3p + -3p Combine like terms: 7p + -3p = 4p -12 + 4p = -5 + 3p + -3p Combine like terms: 3p + -3p = 0 -12 + 4p = -5 + 0 -12 + 4p = -5 Add '12' to each side of the equation. -12 + 12 + 4p = -5 + 12 Combine like terms: -12 + 12 = 0 0 + 4p = -5 + 12 4p = -5 + 12 Combine like terms: -5 + 12 = 7 4p = 7 Divide each side by '4'. p = 1.75 Simplifying p = 1.75
| n^2+7n-18=0 | | 6(3-2x)+8x=9 | | (5y+4)(y+6)=-4(5y+4) | | -1=5x^2-9x+2 | | 2n-12=53 | | -96+2x=-8x+34 | | 108x^2+63xy+9y^2= | | c(q)6000+10qR(q)=12q | | 8x-9(x+1)=3(5-x) | | d=3e | | 8x=5x+4+5 | | C(q)=600+10q | | x^4-31x^2-180=0 | | 2x+9x-2=33 | | -y+6+3y=-5+y | | -12=-2h+.2(20-6h) | | 5x-71=x+41 | | 4p+21=11p | | 3x+6x-4=4-6 | | 3(2x+1)+4x=43 | | -x-2x-4=3 | | x-4*2x=240 | | 15-(3-4x)=2(y+2) | | (2x-4)x=240 | | 6x^2+3=5x | | x^2-10x-18=0 | | 3(2x+3)+4=-59 | | 8x-2y=-44 | | 12+(x+3)-3x=117 | | 3(2x+3)+4x=-59 | | c(q)+6000+10qR(q)=12 | | x*x-4=240 |